The leather couch : clinical practice with kinky clients - Goerlich, Stefani (New York, NY : Routledge, 2021)
"The Leather Couch provides a comprehensive overview of the BDSM and kink community and guides clinicians on how to meet the unique relational and mental health needs of its members. Written in a conversational, accessible style for clinicians and members of the BDSM community alike, The Leather Couch is the go-to resource for any mental health professional or educator looking to transform their practice from kink aware to kink affirming"--
OCLC-licensed vendor bibliographic record.
Keywords: Bondage (Sexual behavior) -- Psychological aspects; Sexual dominance and submission -- Psychological aspects; Sex (Psychology); PSYCHOLOGY / Mental Health; PSYCHOLOGY / Psychotherapy / Couples & Family